2022
DOI: 10.3390/ijms232315045
|View full text |Cite
|
Sign up to set email alerts
|

Polyenic Antibiotics and Other Antifungal Compounds Produced by Hemolytic Streptomyces Species

Abstract: Streptomyces are of great interest in the pharmaceutical industry as they produce a plethora of secondary metabolites that act as antibacterial and antifungal agents. They may thrive on their own in the soil, or associate with other organisms, such as plants or invertebrates. Some soil-derived strains exhibit hemolytic properties when cultivated on blood agar, raising the question of whether hemolysis could be a virulence factor of the bacteria. In this work we examined hemolytic compound production in 23 β-he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 118 publications
0
1
0
Order By: Relevance
“…UPLC-MS results showed that the active substance in SZF-179 against A. alternata was a class of polyene; however, polyene compounds are not very stable and difficult to purify [24]; so, using Saccharomyces cerevisiae as target, we tested the stability of SZF-179 fermentation broth under different temperatures and pHs. Temperature sensitivity experiment results showed that, when the temperature was below 50 • C, the active substance was relatively stable, and the size of the antifungal zone was the same as that in the control.…”
Section: Thermal and Ph Stability Of Szf-179 Fermentation Brothmentioning
confidence: 99%
“…UPLC-MS results showed that the active substance in SZF-179 against A. alternata was a class of polyene; however, polyene compounds are not very stable and difficult to purify [24]; so, using Saccharomyces cerevisiae as target, we tested the stability of SZF-179 fermentation broth under different temperatures and pHs. Temperature sensitivity experiment results showed that, when the temperature was below 50 • C, the active substance was relatively stable, and the size of the antifungal zone was the same as that in the control.…”
Section: Thermal and Ph Stability Of Szf-179 Fermentation Brothmentioning
confidence: 99%